Biological Applications of Thiosemicarbazones and Their Metal Complexes - Shim, Jaesool; Rama Jyothi, N.; Mohammad Farook, N.A. (Asian Journal of Chemistry, 2013)
In this paper, we reviewed antimalarial, antibacterial, antitrypanosomal and antiviral properties of thiosemicarbazones and their metal complexes reported since 2008.